Mechanism of the Yb-Er energy transfer in fluorozirconate glass - da Vila, L. D.; Gomes, L.; Tarelho, LVG; Ribeiro, SJL; Messadeq, Y. (American Institute of Physics (AIP), 2003)
The mechanism of the Yb(3+)-->Er(3+) energy transfer as a function of the donor and the acceptor concentration was investigated in Yb(3+)-Er(3+) codoped fluorozirconate glass. The luminescence decay curves were measured and analyzed by monitoring the Er(3+)((4)I(11/2)) fluorescence induced by the Yb(3+)((2)F(5/2)) excitation. The energy transfer microparameters were determined and used to estimate the Yb-Er transfer rate of an energy transfer process assisted by excitation migration among donors state (diffusion model). The experimental transfer rates were determined from the best fitting of the acceptor luminescence decay obtained using a theoretical approach analog to that one used in the Inokuti-Hirayama model for the donor luminescence decay. The obtained values of transfer parameter gamma [gamma(exp)] were always higher than that predicted by the Inokuti-Hirayama model. Also, the experimental transfer rate, gamma(2)(exp), was observed to be higher than the transfer rate predicted by the migration model. Assuming a random distribution among excited donors at the initial time (t=0) and that a fast excitation migration, which occurs in a very short time (t<gamma(-2)), reducing the mean distance between donor (excited) and acceptor, all the observed results could be explained. (C) 2003 American Institute of Physics.